Proses Berpikir Kreatif Siswa SMP dalam Memecahkan Masalah Bilangan Bulat - Dominggus Ole Dewa; Welas Listiani (Peneliti.net, 2023)
Learning mathematics requires students to have good creative skills. This study aims to describe the critical thinking skills of grade VII students of SMPK Sta. Maria De Lourdes Radaloko. This type of research is qualitative descriptive research. The instruments used are tests and interviews. The study subjects consisted of 3 students selected by purposive sampling. Students have good problem-solving skills in accordance with the problem-solving steps delivered by Polya. The criteria of creative thinking in terms of fluency and flexibility indicate that students have not used many ideas or ways in solving problems. Although in terms of authenticity and detail, students already have unique and detailed answers. The average creative thinking ability of students reaches 55% so that it is in the criteria of being quite creative.